Libertie ebook A novel. - Greenidge, Kaitlyn (2021)
A New York Times 100 Notable Books of 2021 and Best Historical Fiction Pick A Best Book of the Year: Washington Post , TIME , Los Angeles Times , and Christian Science Monitor   “A stunning look at what freedom really means.” — The New York Times   Coming of age in a free Black community in Reconstruction-era Brooklyn, Libertie Sampson is all too aware that her mother, a physician, has a vision for their future together: Libertie is to go to medical school and practice alongside her. But Libertie is hungry for something else—is there really only one way to be independent? And she is constantly reminded that, unlike her light-skinned mother, she will not be able to pass for white. When a young man from Haiti proposes to Libertie and promises a better life on the island, she accepts, only to discover that she is still subordinate to him and all men. As she tries to parse what freedom actually means for a Black woman, Libertie struggles with where she might find it—for herself and for generations to come.   Inspired by the life of one of the first Black female doctors in the United States, critically acclaimed and Whiting Award–winning author Kaitlyn Greenidge returns with an unforgettable and immersive novel that will resonate with readers eager to understand our present through a deep, moving, and lyrical dive into our past.